Microaerophilic Fe(II)-Oxidizing Zetaproteobacteria Isolated from Low-Fe Marine Coastal Sediments: Physiology and Composition of Their Twisted Stalks - Laufer, K. (Appl Environ Microbiol, 2017)
Microaerophilic Fe(II) oxidizers are commonly found in habitats containing elevated Fe(II) and low O(2) concentrations and often produce characteristic Fe mineral structures, so-called twisted stalks or tubular sheaths. Isolates originating from freshwater habitats are all members of the Betaproteobacteria, while isolates from marine habitats belong almost exclusively to the Zetaproteobacteria. So far, only a few isolates of marine microaerophilic Fe(II) oxidizers have been described, all of which are obligate microaerophilic Fe(II) oxidizers and have been thought to be restricted to Fe-rich systems. Here, we present two new isolates of marine microaerophilic Fe(II)-oxidizing Zetaproteobacteria that originate from typical coastal marine sediments containing only low Fe concentrations (2 to 11 mg of total Fe/g of sediment [dry weight]; 70 to 100 μM dissolved Fe(2+) in the porewater). The two novel Zetaproteobacteria share characteristic physiological properties of the Zetaproteobacteria group, even though they come from low-Fe environments: the isolates are obligate microaerophilic Fe(II) oxidizers and, like most isolated Zetaproteobacteria, they produce twisted stalks. We found a low organic carbon content in the stalks (∼0.3 wt%), with mostly polysaccharides and saturated aliphatic chains (most likely lipids). The Fe minerals in the stalks were identified as lepidocrocite and possibly ferrihydrite. Immobilization experiments with Ni(2+) showed that the stalks can function as a sink for trace metals. Our findings show that obligate microaerophilic Fe(II) oxidizers belonging to the Zetaproteobacteria group are not restricted to Fe-rich environments but can also be found in low-Fe marine environments, which increases their overall importance for the global biogeochemical Fe cycle. IMPORTANCE So far, only a few isolates of benthic marine microaerophilic Fe(II) oxidizers belonging to the Zetaproteobacteria exist, and most isolates were obtained from habitats containing elevated Fe concentrations. Consequently, it was thought that these microorganisms are important mainly in habitats with high Fe concentrations. The two novel isolates of Zetaproteobacteria that are presented in the present study were isolated from typical coastal marine sediments that do not contain elevated Fe concentrations. This increases the knowledge about possible habitats in which Zetaproteobacteria can exist. Furthermore, we show that the physiology and the typical organo-mineral structures (twisted stalks) that are produced by the isolates do not notably differ from the physiology and the cell-mineral structures of isolates from environments with high Fe concentrations. We also showed that the organo-mineral structures can function as a sink for trace metals.